Study of stress-strain state of wheelset of freight car during braking - А. А. Krutko; D. A. Sedykh; А. А. Vorobev; A. R. Putintseva; Yu. O. Filippov (Омский научный вестник)
Аs a result of the study, a three-dimensional finite element model of a wheelset with rail sections is developed using a finite element of the ten-node tetrahedron type, and the maximum tangent stresses and maximum equivalent stresses are determined according to the theory of Mises and Dang Wang. It is shown that the maximum shear stresses are observed at a point located at a depth of 4,5–5,3 mm below the surface of the wheel. In case of emergency (short) braking, the maximum stresses take place on the surface of the wheel. With prolonged braking (the movement of the train on a long descent), maximum stresses occur at the point of transition from the disk to the rim on the inside of the wheel, and the value of these stresses is 2,5 times higher than in emergency braking mode. The finite element method is used to determine the stress-strain state of the wheelset of a freight car during braking.